Infant Odontogenic Myxoma: Case Report and Literature Review of a Specific Entity Recently Described - Elena Ruíz Bravo-Burguillos; Jose Juan Pozo Kreilinger; Jesús Manuel Muñoz Caro; Antonio Ríos Parra (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2016)
Odontogenic myxomas are benign mesenchymal neoplasm most of them diagnosed in adults. They are uncommon in the paediatric population and exceptional in infants, with only 21 cases reported in the literature under the age of 2 years. We present a new case of infant odontogenic myxoma, that share the same clinical and radiological presentation with the cases described in the literature. They all presented with a painless paranasal swelling of short-term evolution, usually a few weeks duration (while in children or adults tumours usually develop slowly) and a well-defined, intraosseous, expansible lytic tumour of 3 cm average size in CT-scan examination. Most cases underwent enucleation and curettage with a very low rate of recurrences (4.76%). The aim of this article is to report a new case of this exceptional tumour, whose diagnosis was established at histologic examination. We focus on the importance to undergo a conservative approach in this infant population to minimize the surgical morbidity